Characterization of pediatric head and neck masses with quantitative analysis of diffusion-weighted imaging and measurement of apparent diffusion coefficients - Baiomy, Ali; Nada, Ayman; Gabr, Ahmed; Youssef, Ayda; Mahmoud, Esmat; Zaky, Iman (Indian Journal of Radiology and Imaging, 2020)
Purpose: Our objective was to investigate the accuracy of quantitative diffusion-weighted imaging (DWI) to determine the histopathologic diagnosis of pediatric head and neck lesions. Materials and Methods: This retrospective study included 100 pediatric patients recently diagnosed with head and neck tumors. All patients underwent preoperative conventional magnetic resonance imaging (MRI) and DWI. Each lesion was evaluated according to signal characteristics, enhancement pattern, and diffusivity. The average apparent diffusion coefficient (ADC) obtained from each tumor was compared to the histological diagnosis of benign, locally malignant, or malignant categories. Results: Our retrospective study showed a significant negative correlation between average ADC and tumor histopathologic diagnosis (P < 0.001, r = -0.54). The mean ADC values of benign, locally malignant lesions, and malignant tumors were 1.65 ± 0.58 × 10−3, 1.43 ± 0.17 × 10−3, and 0.83 ± 0.23 × 10−3 mm2 s−1, respectively. The ADC values of benign and locally malignant lesions were overlapped. We found a cut-off value of ≥1.19 × 10–3 mm2s−1 to differentiate benign from malignant pediatric head and neck masses with a sensitivity of 97.3’, specificity of 80.0’, positive predictive value of 94.7’, and negative predictive value of 88.9’. Conclusion: Diffusion-weighted MRI study is an accurate, fast, noninvasive, and nonenhanced technique that can be used to characterize head and neck lesions. DWI helps to differentiate malignant from benign lesions based on calculated ADC values. Additionally, DWI is helpful to guide biopsy target sites and decrease the rate of unnecessary invasive procedures.
Keywords: Apparent diffusion coefficient; DWI; head and neck masses; pediatric